Chief Executive Officer/ Managing Director succession and value relevance of accounting numbers - Sharifah Zarina Syed Ahmad; Mohamat Sabri Hassan; Romlah Jaffar (Penerbit Universiti Kebangsaan Malaysia, 2016)
Apart from Board of Director, top management, including Chief Executive Officer or Managing Director is also considered as an important governance mechanism of the firm. CEO plays a major role in managing and controlling business operations, thus his/her succession may significantly affect firm performance. This study aims to examine the effect of top management succession on share price. Past studies, which used the event-study methodology to evaluate immediate investors’ reactions towards top management succession had their observations done over limited time frame (window periods). Succession may impact the share price beyond the window period because the investors may use information obtained from financial statements to evaluate new top management capabilities. This study contributes to the literature by examining the effects of top management succession on share price at the end of financial years. Book value of equity per share (BE) and earnings per share (EPS) on share price is regressed at three different points of time; year of top management change (TMC), a year after top management change (TMC_1) and post occurrence years of top management change (TMC_C). Findings indicate that BE and EPS are value relevant. Findings also indicate that top management succession is not significantly related to changes in share price over a short period of time (transition year and a post transition year). However, over the longer period of time (TMC_C), our study indicates the top management succession is value relevant. Findings indicate that investors take a longer time to appreciate the new top management on their decision makings. Further analysis indicates that BE is regarded as value relevant by the investors after incorporating firm with outside successor; while EPS is value relevant for the firm with inside successor. This study supports the limited studies in Malaysia which indicate succession events have an implication on share price. Findings in this study may contribute towards strategic decision making in corporate management of public listed companies in Malaysia, specifically when board of directors are considering the top management replacement.